Steel sheet and method for manufacturing the same
A martensitic steel sheet with a controlled chemical composition and manufacturing process improves ductility and lowers the yield ratio, addressing the limitations of existing martensitic steel sheets for automobile applications.
Patent Information
- Application Number
- JP2024062940
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-04-09
- Publication Date
- 2025-01-20
AI Technical Summary
Martensitic steel sheets exhibit poor ductility and high yield ratios, making them unsuitable for automobile parts, despite their high strength potential.
A martensitic steel sheet with a specific chemical composition (C: 0.15-0.25%, Si: 0.70% or less, Mn: 1.10-2.50%, Al: 0.150% or less, P: 0.020% or less, S: 0.010% or less, N: 0.010% or less, Fe and unavoidable impurities) and a controlled number density of carbides with an aspect ratio of 2.0 or more, combined with a manufacturing process involving heating, quenching, and tempering.
The solution results in a martensitic steel sheet with sufficient ductility and a low yield ratio, suitable for automobile parts, achieving an elongation of 6.7% or more and a yield ratio of 0.860 or less, while maintaining high tensile strength.
Smart Images

Figure 2025009816000004 
Figure 2025009816000005 
Figure 2025009816000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to steel sheets and methods for producing the same. [Background technology]
[0002] There has been a demand for improved safety for vehicle occupants, and for this purpose, the strength of the vehicle body has been improved. On the other hand, against the background of the worsening problem of global warming, there is an accelerating movement to improve the fuel efficiency of automobiles. It is known that reducing the weight of the vehicle body is an effective way to improve fuel efficiency.
[0003] In order to improve the safety and reduce the weight of automobile bodies, there is a demand for even stronger steel sheets for automobiles, and the application of steel sheets containing tempered martensite structures (e.g., 95% or more by area) (hereinafter also referred to as "martensitic steel sheets") is being considered. Martensitic steel sheets have the advantage that they can easily achieve high strength with small amounts of added elements.
[0004] Patent Document 1 discloses a martensitic steel sheet having improved delayed fracture resistance, and Patent Document 2 discloses a martensitic steel sheet having improved crash resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 7140301 [Patent Document 2] Patent No. 7120461 Summary of the Invention [Problem to be solved by the invention]
[0006] Although martensitic steel sheets can easily achieve high strength, the structure has poor ductility, making it difficult to apply them to automotive parts from the standpoint of workability. In addition, when considering application to automotive parts, martensitic steel sheets need to have a relatively low yield ratio so as to be less susceptible to fracture.
[0007] In order to improve ductility, it is common to introduce soft phases such as ferrite and / or residual γ, and little research has been done on improving the ductility of martensite structure steel sheets, including in Patent Document 1. In addition, little research has been done on lowering the yield ratio, including in Patent Document 1.
[0008] The present disclosure has been made in light of the above circumstances, and one of its objectives is to provide a martensitic steel sheet having sufficient ductility and a sufficiently low yield ratio, and a manufacturing method thereof. [Means for solving the problem]
[0009] Aspect 1 of the present invention is The composition of the components is C: 0.15~0.25% by mass, Si: 0.70 mass% or less (including 0 mass%) Mn: 1.10~2.50% by mass, Al: 0.150 mass% or less (excluding 0 mass%) P: 0.020% by mass or less (including 0% by mass), S: 0.010% by mass or less (including 0% by mass), and N: 0.010 mass% or less (including 0 mass%), with the balance being Fe and unavoidable impurities; The metal structure contains a tempered martensite structure of 95% or more by area, The density of carbides with an aspect ratio of 2.0 or more is 0.60 / μm 2 The following is a steel plate.
[0010] Aspect 2 of the present invention is The steel sheet according to embodiment 1, further comprising at least one selected from the group consisting of Ti: 0.010 to 0.070 mass%, B: 0.0100 mass% or less (excluding 0 mass%), and Cr: 2.00 mass% or less (excluding 0 mass%).
[0011] Aspect 3 of the present invention is The steel sheet according to aspect 1 or 2, further comprising at least one selected from the group consisting of Cu: 0.50 mass % or less (excluding 0 mass %) and Ni: 0.50 mass % or less (excluding 0 mass %).
[0012] A fourth aspect of the present invention is The steel sheet according to any one of aspects 1 to 3, further comprising at least one selected from the group consisting of V: 0.10 mass % or less (excluding 0 mass %) and Nb: 0.10 mass % or less (excluding 0 mass %).
[0013] A fifth aspect of the present invention is The number density of carbides with an aspect ratio of 2.0 to 2.5 is 0.50 pieces / μm 2 The steel sheet according to any one of the first to fourth aspects is as follows:
[0014] A sixth aspect of the present invention is A step of heating to a first temperature range of 840°C to 950°C and holding the temperature for 30 seconds or more; After the holding step, a step of quenching from a second temperature range, which is 450°C to the first temperature range, to less than 100°C, in which the average cooling rate from 420°C to 250°C is 300°C / sec or more; The method for producing a steel sheet according to any one of aspects 1 to 5, further comprising the step of performing tempering in a third temperature range of 100 to 300° C. for 30 seconds or longer after the quenching step. Effect of the Invention
[0015] According to the embodiments of the present invention, it is possible to provide a martensitic steel sheet having sufficient ductility and a method for producing the same. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic top view of a test piece for measuring the number density of carbides having each aspect ratio, as viewed in the plate thickness direction. [Diagram 2] FIG. 2 is a schematic top view showing the positions of thermocouples in a steel plate during quenching in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventors have conducted research from various angles in order to realize a martensitic steel sheet having sufficient ductility and a sufficiently low yield ratio, and have found that by adjusting the chemical composition to a predetermined value and controlling the number density of carbides having an aspect ratio of 2.0 or more to a predetermined value or less, a martensitic steel sheet having sufficient ductility and a sufficiently low yield ratio can be realized. The following provides details of each requirement stipulated by the embodiment of the present invention.
[0018] <1. Ingredient composition> The steel sheet according to an embodiment of the present invention preferably has a chemical composition including C: 0.15 to 0.25 mass%, Si: 0.70 mass% or less (including 0 mass%), Mn: 1.10 to 2.50 mass%, Al: 0.150 mass% or less (including 0 mass%), P: 0.020 mass% or less (including 0 mass%), S: 0.010 mass% or less (including 0 mass%), and N: 0.010 mass% or less (including 0 mass%), with the balance being Fe and unavoidable impurities. Each element will be described in detail below.
[0019] (C:0.15~0.25% by mass) C is an element necessary for ensuring strength. Therefore, the C content is set to 0.15 mass% or more, preferably 0.16 mass% or more, more preferably 0.17 mass% or more, and even more preferably 0.18 mass% or more. However, if the C content is excessive, the weldability deteriorates. Therefore, the C content is set to 0.25 mass% or less, preferably 0.24 mass% or less, more preferably 0.23 mass% or less, and even more preferably 0.22 mass% or less.
[0020] (Si: 0.70 mass% or less (including 0 mass%)) Si is an element that may be optionally contained. Si may be an element effective in improving the strength by temper softening resistance and solid solution strengthening. It may also be an element effective in suppressing the growth of carbides during the quenching process. In order to exert these effects, the Si content may be more than 0 mass%, and is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, even more preferably 0.15 mass% or more, and even more preferably 0.20 mass% or more. However, since Si is a ferrite generating element, if it is contained in a large amount, the hardenability is impaired, making it difficult to ensure high strength, and the weldability is also deteriorated. Therefore, the Si content is set to 0.70 mass% or less, preferably 0.60 mass% or less, more preferably 0.50 mass% or less, and even more preferably 0.40 mass% or less. In this specification, "including 0 mass%" means that it includes embodiments in which it is not added intentionally, i.e., the content is below the unavoidable impurity level (it does not exclude the case where it is added intentionally).
[0021] (Mn:1.10~2.50% by mass) Mn is an element effective in improving hardenability and increasing strength. It is also an element effective in suppressing the growth of carbides during the hardening process. In order to exert such effects, the Mn content is 1.10 mass% or more, preferably 1.50 mass% or more, more preferably 1.60 mass% or more, even more preferably 1.70 mass% or more, and even more preferably 1.80 mass% or more. However, if the Mn content is excessive, delayed fracture resistance and weldability deteriorate. Therefore, the Mn content is 2.50 mass% or less, preferably 2.40 mass% or less, more preferably 2.30 mass% or less, and even more preferably 2.20 mass% or less.
[0022] (Al: 0.150 mass% or less (excluding 0 mass%)) Al is an element added as a deoxidizer, and also has the effect of improving the corrosion resistance of steel. To fully exert these effects, the Al content is more than 0 mass%, preferably 0.010 mass% or more, more preferably 0.020 mass% or more, even more preferably 0.030 mass% or more, and even more preferably 0.040 mass% or more. However, if Al is contained in excess, a large amount of C-based inclusions are generated, which causes surface defects. Therefore, the Al content is 0.150 mass% or less, preferably 0.140 mass% or less, more preferably 0.130 mass% or less, and even more preferably 0.120 mass% or less.
[0023] (P: 0.020% by mass or less (including 0% by mass)) P (phosphorus) is an inevitable impurity that reduces ductility due to brittleness, so the P content is set to 0.020 mass % or less, preferably 0.015 mass % or less, and more preferably 0.010 mass % or less.
[0024] (S: 0.010% by mass or less (including 0% by mass)) S is an inevitable impurity that generates sulfide-based inclusions and deteriorates the workability and weldability of the base metal, so the S content is set to 0.010 mass% or less, preferably 0.005 mass% or less, and more preferably 0.003 mass% or less.
[0025] (N: 0.010% by mass or less (including 0% by mass)) N is an inevitable impurity, and increases the amount of nitride precipitation, adversely affecting toughness. Therefore, the N content is set to 0.010 mass% or less, preferably 0.008 mass% or less, and more preferably 0.006 mass% or less. On the other hand, in consideration of the steelmaking cost, the N content may be 0.001 mass% or more.
[0026] The steel sheet according to the embodiment of the present invention preferably contains the above-mentioned composition, and in one embodiment of the present invention, the balance is preferably iron and inevitable impurities. As inevitable impurities, the inclusion of trace elements brought in due to the conditions of raw materials, materials, manufacturing equipment, etc. is permitted. Note that, for example, there are elements such as P, S, and N, which are usually preferable to have a smaller content and are therefore inevitable impurities, but whose composition ranges are separately specified as above. For this reason, in this specification, when the term "unavoidable impurities" is used, it is a concept excluding elements whose composition ranges are separately specified.
[0027] As a preferred embodiment of the present invention, in addition to the above elements, it is also effective to further contain, as necessary, (a) at least one selected from the group consisting of Ti: 0.010 to 0.070 mass%, B: 0.0100 mass% or less (excluding 0 mass%), and Cr: 2.00 mass% or less (excluding 0 mass%), (b) at least one selected from the group consisting of Cu: 0.50 mass% or less (excluding 0 mass%) and Ni: 0.50 mass% or less (excluding 0 mass%), (c) at least one selected from the group consisting of V: 0.10 mass% or less (excluding 0 mass%) and Nb: 0.10 mass% or less (excluding 0 mass%), etc., and the properties of the steel sheet are further improved depending on the type of element contained.
[0028] ((a) at least one selected from the group consisting of Ti: 0.010 to 0.070 mass%, B: 0.0100 mass% or less (excluding 0 mass%), and Cr: 2.00 mass% or less (excluding 0 mass%)) Ti is an element that is effective in improving delayed fracture resistance by refining the prior γ grain size through carbide precipitation. Therefore, the Ti content is preferably 0.010 mass% or more, more preferably 0.015 mass% or more, even more preferably 0.020 mass% or more, and even more preferably 0.025 mass% or more. However, excessive Ti content increases the precipitation of carbonitrides, deteriorating the ductility and workability of the base material. Therefore, when Ti is contained, its content is 0.070 mass% or less, preferably 0.060 mass% or less, more preferably 0.050 mass% or less, and even more preferably 0.040 mass% or less. B is an element that improves hardenability with a small amount of addition. In order to fully exert this effect, the B content may be more than 0 mass%, and is preferably 0.0001 mass% or more, more preferably 0.0003 mass% or more, even more preferably 0.0005 mass% or more, and even more preferably 0.0007 mass% or more. However, if B is contained in excess, ductility decreases. Therefore, when B is contained, its content is 0.0100 mass% or less, preferably 0.0090 mass% or less, more preferably 0.0080 mass% or less, and even more preferably 0.0070 mass% or less. Cr is an element effective in increasing strength by improving hardenability. Cr is also an element effective in increasing temper softening resistance of the martensite phase. In order to exert these effects, the Cr content may be more than 0 mass%, and is preferably 0.10 mass% or more, more preferably 0.20 mass% or more, even more preferably 0.30 mass% or more, and even more preferably 0.40 mass% or more. However, if Cr is contained in excess, the delayed fracture resistance property deteriorates. Therefore, when Cr is contained, the content is 2.00 mass% or less, preferably 1.80 mass% or less, more preferably 1.60 mass% or less, and even more preferably 1.40 mass% or less.
[0029] ((b) At least one selected from the group consisting of Cu: 0.50% by mass or less (excluding 0% by mass) and Ni: 0.50% by mass or less (excluding 0% by mass) Cu is an element effective in improving corrosion resistance and delayed fracture resistance. To achieve this effect, the Cu content may be more than 0 mass%, and is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, even more preferably 0.05 mass% or more, and even more preferably 0.07 mass% or more. However, if Cu is contained in excess, ductility and workability are reduced. Therefore, when Cu is contained, its content is 0.50 mass% or less, preferably 0.40 mass% or less, more preferably 0.30 mass% or less, and even more preferably 0.20 mass% or less. Ni is an element effective in improving corrosion resistance and delayed fracture resistance. To achieve this effect, the Ni content may be more than 0 mass%, and is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, even more preferably 0.05 mass% or more, and even more preferably 0.07 mass% or more. However, excessive Ni content reduces ductility and workability. Therefore, when Ni is contained, its content is 0.50 mass% or less, preferably 0.40 mass% or less, more preferably 0.30 mass% or less, and even more preferably 0.20 mass% or less.
[0030] ((c) At least one selected from the group consisting of V: 0.10% by mass or less (excluding 0% by mass) and Nb: 0.10% by mass or less (excluding 0% by mass) V is an element effective in improving strength by precipitation of carbides. To achieve this effect, the V content may be more than 0 mass%, and is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, even more preferably 0.03 mass% or more, and even more preferably 0.04 mass% or more. However, if V is contained in excess, the precipitation of carbonitrides increases, and the ductility and workability of the base material decrease. Therefore, when V is contained, its content is 0.10 mass% or less, preferably 0.09 mass% or less, more preferably 0.08 mass% or less, and even more preferably 0.07 mass% or less. Nb is an element that is effective in improving strength by precipitation of carbides. In order to exert this effect, the Nb content may be more than 0 mass%, and is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, even more preferably 0.03 mass% or more, and even more preferably 0.04 mass% or more. However, if Nb is contained in excess, the precipitation of carbonitrides increases, and the ductility and workability of the base material decrease. Therefore, when Nb is contained, its content is 0.10 mass% or less, preferably 0.09 mass% or less, more preferably 0.08 mass% or less, and even more preferably 0.07 mass% or less.
[0031] Furthermore, as other elements, for example, any one or more selected from the group consisting of Se, As, Sb, Pb, Sn, Bi, Mg, Zn, Zr, W, Cs, Rb, Ca, Co, La, Tl, Nd, Y, In, Be, Hf, Tc, Ta and O (these may be unavoidable impurities) may be contained in an amount of up to 0.01 mass% (including 0 mass%) in total as necessary in order to improve the corrosion resistance and delayed fracture resistance of the base material.
[0032] <2.Metal structure> In the steel sheet according to the embodiment of the present invention, the metal structure contains a tempered martensite structure of 95% or more by area, preferably 97% or more by area, and the upper limit of the area ratio of the tempered martensite structure is not particularly limited and may be 100% by area. The metal structure of the steel sheet according to the embodiment of the present invention may include, in addition to the tempered martensite structure, one or more structures that are inevitably included in the manufacturing process, such as a ferrite structure, a bainite structure, a retained austenite (γ) structure, and an as-quenched martensite structure. The area ratio of the tempered martensite structure can be determined by the method described in the examples below.
[0033] <3. Carbide> The inventors discovered that carbides with a high aspect ratio, which may exist mainly at grain boundaries in martensitic steel sheets, embrittle the grain boundaries and reduce ductility. They then adjusted the composition to a given level and reduced the number density of carbides with an aspect ratio of 2.0 or more to 0.60 / μm 2 It has been found that a martensitic steel sheet having sufficient ductility can be realized by the following. Furthermore, when considering application to automobile parts, etc., it is preferable that the yield ratio is not too high because it is less likely to break. 2 It was found that the yield ratio could be sufficiently reduced by setting the following. The "aspect ratio" here is the value obtained by dividing the length in the longitudinal direction by the short diameter (the maximum length in the direction perpendicular to the longitudinal direction) when the carbide is viewed in plan view by a SEM or the like (longitudinal length / short diameter). The number density of carbides with an aspect ratio of 2.0 or more is preferably 0.50 pieces / μm 2 Less than or equal to 0.40 particles / μm, more preferably 0.40 particles / μm 2 Less than or equal to 0.30 particles / μm, more preferably 0.30 particles / μm 2 The upper limit of the aspect ratio is not particularly limited, but considering the range that is likely to exist in the production method described below, it may be, for example, 5.5 or less. The number density of carbides having an aspect ratio of 2.0 or more can be determined by the method described in the Examples below. When determining the number density of the carbides, carbides having a circle-equivalent diameter of 0.0245 μm or more can be counted. If the circle-equivalent diameter of the carbides is less than 0.0245 μm, the carbides do not grow sufficiently, and it is considered that carbides having a high aspect ratio that affects ductility are unlikely to exist.
[0034] The steel sheet according to the embodiment of the present invention has a number density of carbides having an aspect ratio of 2.0 to 2.5 of 0.50 pieces / μm 2It is preferable that the number density of carbides having an aspect ratio of 2.0 to 2.5 is 0.45 pieces / μm or less. It is considered that carbides having an aspect ratio of 2.0 to 2.5 are likely to precipitate in large quantities during the quenching process, and by suppressing the precipitation of the carbides, the ductility can be further improved, and further, the yield ratio can be easily controlled to a predetermined value or less. The number density of carbides having an aspect ratio of 2.0 to 2.5 is more preferably 0.45 pieces / μm 2 Less than or equal to 0.40 particles / μm, more preferably 0.40 particles / μm 2 Less than or equal to 0.35 particles / μm, more preferably 0.35 particles / μm 2 The following is the result. The number density of carbides having an aspect ratio of 2.0 to 2.5 can be determined by the method described in the Examples below. When determining the number density of the carbides, carbides having an equivalent circle diameter of 0.0245 μm or more can be counted.
[0035] The steel sheet according to the embodiment of the present invention has sufficient ductility, specifically, elongation of 6.7% or more. The steel sheet according to the embodiment of the present invention also has a sufficiently low yield ratio, specifically, a yield ratio of 0.860 or less. The yield ratio is preferably 0.700 or more, which makes it easier to ensure the yield strength required for automobile parts. Furthermore, the steel sheet according to the embodiment of the present invention is a martensitic steel sheet and has high strength, specifically, a tensile strength of 1270 MPa or more.
[0036] <4. Manufacturing method> The method for producing a steel sheet according to an embodiment of the present invention comprises: (A) heating to a first temperature range of 840°C to 950°C and holding the temperature for 30 seconds or more; (B) after the holding step, a step of quenching from a second temperature range of 450°C to the first temperature range to less than 100°C, wherein the average cooling rate from 420°C to 250°C is 300°C / sec or more; (C) after the quenching step, a step of tempering in a third temperature range of 100 to 300° C. for 30 seconds or more is included. The steel sheet according to the embodiment of the present invention can be manufactured by the above-mentioned method. Each step will be described in detail below.
[0037] (A) A step of heating to a first temperature range and maintaining the temperature for 30 seconds or more. First, a steel sheet is heated to a first temperature range of 840°C to 950°C and held there for 30 seconds or more. The steel sheet to be heated may be, for example, a steel sheet having the above-mentioned composition. The method for preparing the steel sheet having the above-mentioned composition is not particularly limited. For example, the steel sheet may be melted and continuously cast in a conventional manner to obtain a steel billet such as a slab having the above-mentioned composition, and then heated to about 1100°C to 1250°C, hot-rolled, coiled, pickled, and cold-rolled to prepare the steel sheet.
[0038] By setting the first temperature range at 840°C or higher, it becomes possible to form an austenite single phase structure (to later obtain a tempered martensite structure with 95% or more by area). Furthermore, by setting the first temperature range at 950°C or lower, it becomes possible to reduce the equipment load and reduce the manufacturing cost. The heating holding time in the first temperature range needs to be 30 seconds or more in order to complete the austenite transformation. There is no particular upper limit to the heating holding time, but it is preferably 400 seconds or less from the viewpoint of productivity.
[0039] (B) Process of quenching from the second temperature range After step (A), quenching is performed from the second temperature range, which is 450°C to the first temperature range, to less than 100°C (for example, room temperature). If the second temperature range is less than 450, a large amount of bainite and / or autotempered martensite may be generated, and strength may decrease. The upper limit of the second temperature range is the first temperature range, that is, quenching may be performed immediately after step (A). On the other hand, the second temperature range may be less than the first temperature range (450°C or more). In that case, the cooling rate from the first temperature range to the second temperature range is not particularly limited, but it is preferable to set it to, for example, 5°C / second or more from the viewpoint of preventing ferrite from being formed. The quenching method is not particularly limited, and it can be performed by a known method such as water cooling and oil cooling.
[0040] Furthermore, in step (B), the average cooling rate from 420°C to 250°C is set to 300°C / sec or more. The temperature range from 420°C to 250°C corresponds to the temperature range where martensitic transformation starts and ends, and when the martensitic structure transformed in this temperature range is self-tempered, carbides with a high aspect ratio (for example, aspect ratio of 2.0 or more, or 2.0 to 2.5) are likely to precipitate. Therefore, by increasing the cooling rate in this temperature range, the generation of carbides with a high aspect ratio can be suppressed. The average cooling rate from 420°C to 250°C is more preferably 400°C / sec or more, even more preferably 500°C / sec or more, and even more preferably 600°C / sec or more.
[0041] (C) Tempering process After step (B), tempering is performed for 30 seconds or more in a third temperature range of 100 to 300°C. If the third temperature range exceeds 300°C, it becomes difficult to ensure strength. The third temperature range is preferably 280°C or less, more preferably 260°C or less. On the other hand, if the third temperature range is less than 100°C, it becomes difficult to improve toughness.
[0042] The method for manufacturing a steel sheet according to the embodiment of the present invention may include other steps as long as the object of the present invention is achieved. EXAMPLES
[0043] The following examples are provided to more specifically describe the embodiments of the present invention. The embodiments of the present invention are not limited to the following examples, and may be modified as appropriate within the scope of the above and below-described aims, and all of these are included in the technical scope of the embodiments of the present invention.
[0044] Steel billets satisfying the composition of steel types A to H shown in Table 1 (the balance being iron and unavoidable impurities) were obtained by melting and continuous casting according to a conventional method. Thereafter, the billets were heated to 1200°C, then hot-rolled (finishing temperature: 870°C, finishing thickness: 2.6 mm), coiled at 620°C, pickled, and cold-rolled to obtain steel plates with a thickness of 1.4 mm. The obtained steel plates were cut to a size of 150 mm x 160 mm, subjected to the heat treatment described in step (A) of Table 2, and then quenched under the conditions described in step (B) of Table 2. The cooling rate from the heating temperature in step (A) to the quenching start temperature in step (B) of test Nos. 1, 2, 4, 5, 7, 8, 10, 11, 13, 14, 16, 17, 19, 20, 22, and 23 was 5°C / sec or more. The quenching conditions were as follows: the amount of water was 70L to ensure the cooling rate, and the water temperature was room temperature for Test Nos. 1, 2, 4, 5, 7, 8, 10, 11, 13, 14, 16, 17, 19, 20, 22, and 23, and 60°C for Test Nos. 3, 6, 9, 12, 15, 18, 21, and 24 to intentionally slow down the cooling rate. In addition, for Test Nos. 1, 4, 7, 10, 13, 16, 19, and 22, the cooling water was circulated at 1.0 m / min x 0.2 MPa using a water pump to intentionally increase the cooling rate. Figure 2 is a top view schematic diagram showing the positions of thermocouples during quenching of a steel plate cut to 150 mm x 160 mm, as viewed from the plate thickness direction. As shown in Fig. 2, thermocouples 2 (indicated by black circles) were attached to five locations on the steel plate 1, the temperature was measured at a sampling period of 0.01 seconds, and the cooling rate from 420 to 250°C was measured at the five locations, and the average value was taken as the average cooling rate from 420 to 250°C. After quenching, tempering was performed under the conditions shown in step (C) of Table 2. In Table 1, "-" in the "Si", "Cu" and "Cr" columns means that the content was at the level of unavoidable impurities that were not intentionally added. Also, P, S and N were not intentionally added and are at the level of unavoidable impurities, but as mentioned above, their content must be strictly controlled, so their content is disclosed.
[0045] [Table 1]
[0046] [Table 2]
[0047] The steel sheets of Test Nos. 1 to 24 were evaluated as follows.
[0048] <Area ratio of tempered martensite structure> A cross section of a test piece measuring 1.4 mm (thickness direction) x 20 mm (rolling direction) x 20 mm (width direction) parallel to the rolling direction and thickness direction (i.e. perpendicular to the width direction) was polished and subjected to nital etching, after which an SEM image was obtained at 1000x magnification for the 1 / 4t portion (t is the thickness). An arbitrary field of view (field area: 12275 μm 2 ) 10 lines were drawn at equal intervals both horizontally and vertically, and the number of intersections where the tempered martensite structure was located was divided by the total number of intersections to determine the area ratio of the tempered martensite structure. The results are shown in Table 3 below.
[0049] <Tensile properties> For the tensile properties, JIS No. 5 tensile test pieces were taken from the steel plates of test Nos. 1 to 24 so that the plate width direction (i.e., the direction perpendicular to the rolling direction and plate thickness direction) was the longitudinal direction, and tensile strength TS (MPa), yield stress YS (MPa), and elongation EL (%) as ductility were determined according to the method specified in JIS Z 2241. The yield ratio YR was taken as YS / TS. For each physical property value, n=2 tests were performed and the average value was used. The results are shown in Table 3 below.
[0050] <Number density of carbides with each aspect ratio> Figure 1 is a schematic diagram of the top surface of a test piece 1 for measuring the number density of carbides with each aspect ratio, as viewed from the plate thickness direction. As shown in Figure 1, the test piece 1 was cut out from the remaining material after the tensile test so that a cross section S2 2 mm away from the fracture surface S1 could be observed, and after polishing and picral etching, the position t / 2 (t is plate thickness) and the vicinity of the center of the test piece in the rolling direction LD (indicated by the dashed line CL) were observed from the observation direction OD, and FE-SEM images were obtained at a magnification of 5000 times. An arbitrary field of view (field area: 416 μm 2 ), binarization was performed, the longitudinal length and minor axis (maximum length perpendicular to the longitudinal direction) of the carbides displayed in white were measured, and the aspect ratio (longitudinal length / minor axis) of each carbide was obtained. The number of carbides with an aspect ratio of 2.0 or more and the number of carbides with an aspect ratio of 2.0 to 2.5 were obtained, and each number density was calculated by dividing them by the field area. When each number density was obtained, carbides with a circle equivalent diameter of 0.0245 μm or more were counted. The maximum circle equivalent diameter of the counted carbides was 0.227 μm. In addition, in the number density with an aspect ratio of 2.0 or more, the aspect ratios of the counted carbides were all 5.5 or less, and none exceeding 5.5 were confirmed. The results are shown in Table 3.
[0051] [Table 3]
[0052] The following can be seen from Table 3. Test Nos. 1 to 3 and 7 to 24 all satisfied the requirements defined in the embodiment of the present invention, and had sufficient ductility (elongation of 6.7% or more) and a sufficiently low yield ratio (0.860 or less). On the other hand, Test Nos. 4 to 6 did not satisfy the requirements defined in the embodiment of the present invention, and had insufficient ductility and a high yield ratio. Specifically, Test Nos. 4 to 6 all had an insufficient Mn content and a number density of carbides with an aspect ratio of 2 or more of 0.60 pieces / μm 2 Therefore, the elongation was less than 6.7% and the yield ratio was more than 0.860. [Explanation of symbols]
[0053] 1 steel plate 2 Thermocouples
Claims
1. The composition of the components is C: 0.15 to 0.25% by mass, Si: 0.70 mass% or less (including 0 mass%), Mn: 1.10 to 2.50% by mass, Al: 0.150 mass% or less (excluding 0 mass%) P: 0.020% by mass or less (including 0% by mass), S: 0.010% by mass or less (including 0% by mass), and N: 0.010 mass% or less (including 0 mass%), with the balance being Fe and unavoidable impurities; The metal structure contains a tempered martensite structure of 95% or more by area, The number density of carbides with an aspect ratio of 2.0 or more is 0.60 pieces / μm 2 Below is a steel plate.
2. The steel plate according to claim 1, further comprising one or more of the group consisting of the following (a) to (c): (a) at least one selected from the group consisting of Ti: 0.010 to 0.070 mass%, B: 0.0100 mass% or less (excluding 0 mass%), and Cr: 2.00 mass% or less (excluding 0 mass%) (b) at least one selected from the group consisting of Cu: 0.50% by mass or less (excluding 0% by mass) and Ni: 0.50% by mass or less (excluding 0% by mass); (c) at least one selected from the group consisting of V: 0.10% by mass or less (excluding 0% by mass) and Nb: 0.10% by mass or less (excluding 0% by mass);
3. The number density of carbides with an aspect ratio of 2.0 to 2.5 is 0.50 pieces / μm 2 The steel sheet according to claim 1 or 2, wherein:
4. A step of heating to a first temperature range of 840° C. to 950° C. and holding the temperature for 30 seconds or more; After the holding step, a step of quenching from a second temperature range, which is 450°C to the first temperature range, to less than 100°C, wherein the average cooling rate from 420°C to 250°C is 300°C / sec or more; The method for producing a steel plate according to claim 1 or 2, further comprising the step of tempering the steel plate in a third temperature range of 100 to 300° C. for 30 seconds or more after the quenching step.
Citation Information
Patent Citations
steel plate
JP7120461B2
Steel plates, components, and their manufacturing methods
JP7140301B1